Menopausal Symptoms Severity and Its Related Factors - Al- Battawi, Jilan Ali Ibrahim; Essa, Rasha Mohamed (International Journal For Research In Health Sciences And Nursing, 2018)
Recently, menopause has received much attention as a result of increased life expectancy of women and the subsequent postmenopausal conditions precipitating by either estrogen deficiency, such as cardiovascular disease or by osteoporosis, and estrogen dominance, such as breast cancer and endometrial cancer. Menopause is simply defined as the permanent cessation of menses. During this period, the women experience different symptoms due to failure or declining in ovarian function. A wide range of symptoms and signs women are encountered during menopausal period. Aim of the study was determine of Menopausal Symptoms Severity and Its Related Factors. Materials and Method: An explanatory descriptive cross-sectional research design was used to carry out this study. Setting: The study was conducted from December 201 up to February, 2017 at, El-Shatby Maternity University Hospital, Alexandria, Egypt. Subjects: A total of 240 eligible women attending the outpatient clinic at El-Shatby Maternity University Hospital were recruited to participate in the study. Two Tools were used to collect the necessary data for the research. Tool I: Socio-demographic characteristics, menstrual, medical surgical and reproductive history structured interview questionnaire. It was divided into two parts. Part one: Concerned with participants’ Socio-demographic data, menstrual, reproductive, and medical surgical history. Part two: Concerned with personal & social habits. Tool II: Greene Climacteric Scale developed by Greene. Latest version of the statistical software package SPSS (Version-21) was used. Descriptive and analytical statistical test were used to analyze the data. Results: Women with moderate to severe symptoms (≥20) corresponded to 57.7% (116) of the sample. Obesity was not associated with the severity of menopausal symptoms (p < 0.90).Severe to moderate symptoms were inversely associated with age (PR 0.96; CI 95% 0.94–0.99;p < 0.01). Women within 6–10 years of menopause presented nearly 1.4 times higher prevalence of moderate to severe symptoms compared with those with more than 10 years of menopause. Unemployed women (PR 1.52; CI 95% 1.13–2.04; p < 0.01) and housewives (PR1.53; CI 95% 1.12–2.09; p < 0.01) presented higher prevalence of menopausal symptoms com-pared with working women. Tobaccos was associated with higher prevalence of moderate to severe symptoms (p < 0.01). Conclusions: Age constituted a protection factor for moderate to severe symptoms, whereas having within 6–10 years of menopause, smoking and being unemployed or a housewife were factors related to higher prevalence of moderate to severe menopausal symptoms.